2016
DOI: 10.1245/s10434-016-5327-8
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Appropriateness and Value for Breast Surgeons and Their Patients: The American Society of Breast Surgeons Choosing Wisely ® Initiative

Abstract: BackgroundCurrent breast cancer care is based on high-level evidence from randomized, controlled trials. Despite these data, there continues to be variability of breast cancer care, including overutilization of some tests and operations. To reduce overutilization, the American Board of Internal Medicine Choosing Wisely® Campaign recommends that professional organizations provide patients and providers with a list of care practices that may not be necessary. Shared decision making regarding these services is en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…27 Given these observations and the lack of oncologic benefit to additional axillary surgery, the American Society of Breast Surgeons included omission of ALND in appropriate SLN-positive patients in their Choosing Wisely® Campaign. 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Given these observations and the lack of oncologic benefit to additional axillary surgery, the American Society of Breast Surgeons included omission of ALND in appropriate SLN-positive patients in their Choosing Wisely® Campaign. 11 …”
Section: Discussionmentioning
confidence: 99%
“…11 A review of the National Cancer Database reported on >74,000 patients who met Z0011 criteria with 1–2 positive nodes. The proportion of patients undergoing ALND dropped from 94% in 1998 to 77% in 2009 (the year before trial publication) to 44% in 2011 after release of the results (p<.001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous meta-analyses focusing on preoperative MRI have reported solely on its detection capability 13 , or have indicated that MRI could increase mastectomy rates but with equivocal findings for some surgical outcomes 6 . It is not surprising then that guidelines give varying recommendations regarding use of pre-operative MRI in newly diagnosed BC and that there is persistent use of MRI for pre-operative surgical planning in BC 10;17–19 .…”
Section: Introductionmentioning
confidence: 99%
“…First introduced in breast cancer around 2000, the use of perioperative MRI among Medicare beneficiaries increased to 25% in 2008-2009 (22); PET scan use grew to more than 10% by 2006 (23). Though preoperative MRIs have a higher sensitivity for detection of additional breast lesions, randomized studies have not demonstrated survival differences (24,25), and concerns have been raised about the association between MRI and more aggressive surgical care and overdiagnosis (22,26), leading the American Society of Breast Surgeons to recommend against their routine use (27). The American Society of Clinical Oncology has recommended against routine PET scans for breast cancer with a low risk of metastasizing based on retrospective studies (28).…”
mentioning
confidence: 99%